Critical Discourse Analysis of Influencer Language in Building Digital Public Opinion - Sosiana Sosiana (Sean Institute, 2026)
This study aims to analyze influencers' linguistic strategies in building digital public opinion through a Critical Discourse Analysis (CDA) approach. The background of this study is based on the increasing role of social media influencers as digital opinion leaders who not only convey information but also construct social reality through persuasive and ideological language practices. Although various previous studies have highlighted aspects of credibility and engagement , the linguistic dimensions and power relations in influencer discourse are still relatively understudied. This study uses a qualitative descriptive-analytical approach with Fairclough's three-dimensional model that includes text analysis, discursive practices, and social practices. The research data consists of 15 public opinion content from three social media influencers selected purposively based on the level of interaction and issue relevance. The data were analyzed through transcription, discourse segmentation, thematic coding, and critical interpretation stages to identify lexical strategies, syntactic structures, modalities, framing, and representations of social actors. The results show that influencers systematically use evaluative diction, high modality, metaphors, and polarization strategies to frame issues and build certain ideological positions. At the level of discursive practice, the use of inclusive pronouns and personal narratives strengthens the legitimacy of opinions and creates symbolic closeness with the audience. At the level of social practice, influencer discourse operates within a hybrid digital power structure—encouraging public participation while simultaneously reproducing the logic of attention commodification. This study concludes that digital public opinion is formed through structured, rather than spontaneous, discursive processes, and that influencer language plays a strategic role in the construction of social reality. Theoretically, this study expands the application of Critical Discourse Analysis to the study of digital influencers; practically, these findings contribute to strengthening society's critical literacy regarding social media discourse.